CHARACTERIZATION OF ARTISANAL FISHING IN FISHWEIRS, THE NORTH COAST OF PARAIBA, BRAZIL - do Nascimento, Glória Cristina Cornélio; Córdula, Eduardo Beltrão de Lucena; de Lucena, Reinaldo Farias Paiva; Rosa, Ricardo de Souza; Mourão, José da Silva (Arquivos de Ciências do Mar, 2017)
Traditional fishing strategies are used by fishing communities around the world, such as fish-weirs, which are fixed traps built along a coastal zone. This study aims to characterize and describe how fish-weirs are managed by fishermen from the coastal state of Paraíba in the Northeast Brazil. Unplanned interviews, “rapport”,“Snow ball”, and direct observation were carried out during monthly visits to five fish-weirs, from November 2012 to March 2013. We quantified fish-weirs production, and identified the most species caught. These traps are made up of compartments and go through steps both, on land and at sea, until they are completely activated. The total fish production was 303 kg. The predominant species were: Mugil curema and Mugil liza, Trichiurus lepturus,Caranx hippos,Selene vomer and Selene setapinnis, and Diapterus auratus and Diapterus rhombeus. We concluded that this type of fishing has been used for decades on the coast of Paraíba, and that the fishermen have their own management and techniques, used with this type of trap.